1994
DOI: 10.1002/eji.1830240334
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐7 regulates c‐myc expression in murine T cells and thymocytes: a role for tyrosine kinase(s) and calcium mobilization

Abstract: Interleukin-7 (IL-7) was originally identified as a pre-B cell growth factor whose proliferating activity has been extended to numerous target cells including T lymphocytes. We investigated c-myc mRNA expression, an oncogene associated with proliferation, in the murine T cell line D10 G4.1 and freshly isolated thymocytes since both target cells proliferate in response to IL-7. We find that blockade of the tyrosine kinase pathway by genistein, a potent tyrosine kinase inhibitor, inhibits both IL-7-dependent D10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This difference was reflected in a significant task-by-display-size interaction [F(4,56) = 4.47, P < 0.0051 (10).…”
Section: Diabetes and Digestive And Kidney Diseases Grantmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference was reflected in a significant task-by-display-size interaction [F(4,56) = 4.47, P < 0.0051 (10).…”
Section: Diabetes and Digestive And Kidney Diseases Grantmentioning
confidence: 99%
“…The PER protein is predominantly nuclear (5-7) and also accumulates with a circadian rhythm (5,6,8,9). However, PER is most abundant late at night when per RNA levels are low (5,8,9,10). These observations, and the finding that constitutive overexpression of PER protein can substantially diminish the per mRNA rhythm in certain cells of the fly ( l o ) , are consistent with the proposal that PER negatively regulates expression of its own mRNA (3).…”
mentioning
confidence: 99%
“…Recent studies of primary T cells have suggested a robust physiological role for Myc in global transcriptional amplification (12), proliferation (38), reprogramming of the cellular metabolic state upon T cell activation (39), but paradoxically also increased apoptosis (40). We hypothesize that the overexpression of Myc in our CD8+ effector clones may be balanced by the anti-apoptotic and pro-survival effects of BCL6 and/or IL-7R (41) to direct the memory fate of effector cells. However, further mechanistic studies are necessary to define this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that c-myc expression in thymocytes can be enhanced by IL-7 in a tyrosine kinase and Ca^"^-dependent manner (Seckinger et al 1994) and that c-myc induces gene expression of the murine p34"''^^ and cyclin-dependent kinase-2 (cdk-2) homologues in murine T lymphocytes . Although c-myc-induced apoptosis can occur at different stages of the cell cycle (reviewed in White 1993), deregulated activation of cdc-2 kinase leads lo activation-induced cell death through a "mitotic-catastrophe" .…”
Section: Is Negative T-cell Selection a Mitotic Catastrophe?mentioning
confidence: 99%